Development of a Screening Tool to Identify Safer Biodiesels - Landwehr, Katherine (Curtin University, 2021)
Biodiesel is a renewable fuel that can be created from natural fats and oils. Exhaust from an engine running on these fuels changes depending on what they are made out of, however it was not known if health impacts changed also. The aim of this work was to test whether biodiesel made from different oil types altered the toxic impacts of exhaust exposure and generate a ranked list of most to least toxic biodiesel fuels.